Convergent Evolution of a New Arsenic Binding Site in the ArsR/SmtB Family of Metalloregulators, - Qin, Jie (2007)
Acidithiobacillus ferrooxidans has an arsenic resistance operon that is controlled by an As(III)-responsive transcriptional repressor, AfArsR, a member of the ArsR/SmtB family of metalloregulators. AfArsR lacks the As(III) binding site of the ArsRs from plasmid R773 and Escherichia coli, which have a Cys(32)-Val-Cys(34)-Asp-Leu-Cys(37) sequence in the DNA binding site. In contrast, it has three cysteine residues, Cys(95), Cys(96), and Cys(102), that are not present in the R773 and E. coli ArsRs. The results of direct As(III) binding measurements and x-ray absorption spectroscopy show that these three cysteine residues form a 3-coordinate As(III) binding site. DNA binding studies indicate that binding of As(III) to these cysteine residues produces derepression. Homology modeling indicates that As(III) binding sites in AfArsR are located at the ends of antiparallel C-terminal helices in each monomer that form a dimerization domain. These results suggest that the As(III)-S(3) binding sites in AfArsR and R773 ArsR arose independently at spatially distinct locations in their three-dimensional structures.